Zwingli en Leo Jud se Zürichse Doopformulier - Storm, J. G. M. (Hervormde teologiese studies, 1985)
The Zurich Baptismal Formulary of Zwingli and Leo Jud The author expands on Zwingli and Leo Jud's Zurich order of baptism now to be discussed. The sacrament of baptism does not ensure salvation for the pious. All sinners can only be saved by the grace of God. The baptismal ceremony does not entitle the cleansing of sin. It promises the baptized that he is the property of the Lord. Baptism is the sign to show that we are saved from sin by the grace of God. The children of believing Christians can therefore receive baptism as a sign of salvation as children of God, exactly like the children in the time of the Old Testament. They form part of a covenant. In the time of the Old Testament it was known as circumcision - today it is known as baptism.